1996
DOI: 10.1002/(sici)1098-2256(1996)11:1<21::aid-tox4>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

In situ survival of genetically engineered microorganisms in a tropical aquatic environment

Abstract: In this study, the survival of genetically engineered microorganisms (GEMs) and their interactions with the environmental microbiota of a tropical river was investigated. Diffusion chambers were used for the in situ survival experiments with a nonplasmid containing Escherichia coli DH7 strain and two model GEMs, E. coli JM103 containing a 2.6 kilobase plasmid (pUC9) and E. coli DH1 with a 4.8 kb plasmid (pWTAla5'). Pure culture survival studies indicated that after a week in the environment a 1.0 log,, decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…3.17X10 11 1.99X10 10 2.31X10 5 1.69X10 4 2.3X10 3 ‫ــــ‬ ‫ـــــ‬ ‫ـــــ‬ MAM2A 7.28X10 14 3.9X10 10 2.81X10 5 9.68X10 4 3.7X10 3 1. Alvarez et al (1996) suggested that the presence of competing bacteria may limit the survival time of GMMs in the environment. Similar results have been described previously, McClure et al, (1991) found that the level of the introduced strain declined rapidly from 1.8x10 8 to 4.7x10 5 after 6 days, the population of the introduced strain then remained stable for the next 10 days.…”
Section: Pu21amentioning
confidence: 99%
See 4 more Smart Citations
“…3.17X10 11 1.99X10 10 2.31X10 5 1.69X10 4 2.3X10 3 ‫ــــ‬ ‫ـــــ‬ ‫ـــــ‬ MAM2A 7.28X10 14 3.9X10 10 2.81X10 5 9.68X10 4 3.7X10 3 1. Alvarez et al (1996) suggested that the presence of competing bacteria may limit the survival time of GMMs in the environment. Similar results have been described previously, McClure et al, (1991) found that the level of the introduced strain declined rapidly from 1.8x10 8 to 4.7x10 5 after 6 days, the population of the introduced strain then remained stable for the next 10 days.…”
Section: Pu21amentioning
confidence: 99%
“…Kargatova et al (2001) noted a decrease in cfu/ml to 10 2 with in a week. Alvarez et al, (1996) found differences in survival rates between GEMs and suggested that some GEMs are less resilient in the environment. Hong et al, (1996) found that number of 2.4-D-degrading bacteria were declined in natural river water.…”
Section: Pu21amentioning
confidence: 99%
See 3 more Smart Citations